The effects of Instagram beauty advertisements on female university students in Malaysia: a Lavidge and Steiner's Hierarchy Model of Effects and Islamic perspective - Mokhtar, Aida; Armelia, Mila (2021)
INTRODUCTION Instagram is one of the more popular and familiar social media platforms for teenagers nowadays. Most Instagram users generally are women globally (54.2%) (Statista, 2020). With the launch of Instagram advertising, in 2016, it has since provided an alternative to advertisers for their advertisements and e-commerce. This study aimed to examine the influence of Instagram advertisements of beauty products on young female audiences studying in a public university in Malaysia. It adopted the quantitative research design using the online questionnaire framed by Lavidge and Steiner’s Hierarchy of Effects model. The model consists of three main components: Cognitive (Awareness and Knowledge), Affective (Liking and Preference) and Conative (Conviction and Purchase) (Lavidge & Steiner, 1961). The Islamic perspective was also included in the study underscoring the significance of conducting advertisements in an Islamic manner. The Islamic perspective has been associated with Lavidge and Steiner’s model supported by Qur’anic verses and aHadith where each step of the model has an Islamic perspective (Mokhtar, 2016). The findings are useful for advertisers, advertising academicians and advertising agencies that would be interested to know more on the effects of beauty advertisements on Instagram targeted to female university students in Malaysia for them to produce effective advertisements.